(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The maximum and minimum values of lE/Rn (latent heat fluxes/Net radiation) ratio in Aman rice field were 0.63 MJm2, and 0.16 MJm-2, respectively whereas the average value was 0.41 MJm-2 during wet condition. H (Sensible heat fluxes) was positive during the day with few fluctuations and the ratios of H/Rn fluctuated from 0.67 MJm-2 to 0.22 MJm-2 while the average value was 0.45 MJm-2 and this phenomenon was due to available moisture availability in the Aman rice field. The maximum G/Rn ratio was 0.20 MJm-2 while the minimum ratio was 0.09 MJm-2 and their average value was 0.14 MJm-2. The value of G was considerably small due to the canopy architecture in Aman rice cropping system. In post Aman rice field, sensible heat flux density of the fallow rice field showed highest 25.66 MJm-2. On an average, H was 58.6 % of the whole Rn while the minimum and maximum portions were5.68 % and maximum of 114.86 %, respectively in well irrigated fields. The measured average H/Rn ratio was 0.54 MJm-2 in post Aman rice field while their maximum and minimum values were 0.79 MJm-2, 0.07 MJm-2, respectively. The lE/Rn ratios ranged from 0.05 MJm-2 to 0.76 MJm-2 with an average value of 0.30 MJm-2. G/Rn accounted maximum 0.24 MJm-2, minimum 0.07 MJm-2 and on an average 0.16 MJm-2 and G was considerably larger than vegetative fields due to the less crop canopy architecture in post Aman rice fallow field. In Boro rice field variations in Rs mainly observed due to weather condition. H/Rn ratios from the rice field and observed that the maximum 0.88 MJm-2, minimum 0.20 MJm-2 and on an average 0.49 MJm-2, this phenomenon due to seasonal weather characteristics. The lE/Rn ratios in the Boro rice field observed maximum 0.60 MJm-2, minimum 0.04 MJm-2 and on an average 0.35 MJm-2. G accounted maximum 0.22 MJm-2, minimum 0.08 MJm-2 and on an average 0.16 MJm-2 and G was considerably small due to the canopy architecture Boro rice cropping system. In post Boro fallow rice field the maximum value of the ratio of lE/Rn was 0.82 MJm-2 while the minimum value was 0.41 MJm-2 with an average of 0.66 MJm-2. The lE/Rn ratios exhibited the highest ratios among the all observation periods and due to more availability of water. The H/Rn ratios observed maximum 0.50 MJm-2, minimum 0.12 MJm-2 and on an average 0.25 MJm-2. G accounted maximum 0.14MJm-2, minimum 0.06 MJm-2 and on an average 0.09 MJm-2 and G was considerably smaller than vegetative fields due to the less crop canopy architecture and much water availability in post Boro rice fallow field. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22065 J. Environ. Sci. & Natural Resources, 6(1): 195-201 2013